Satisfaction and dissatisfaction in wine tourism: a user-generated content analysis - Meneses, Raquel (2023)
Consumer satisfaction plays a critical role in the success and survival of tourism organizations, including wine tourism. This study aims to identify the determinants of satisfaction and dissatisfaction in wine tourism experiences using a customer-centric approach and analyzing user-generated content. The analysis reveals that satisfaction and dissatisfaction in wine tourism are influenced by different factors, supporting the two- and three-factor theories. Common themes among satisfied and dissatisfied tourists include wine, visits, and related circuits. The study validates online reviews as a valuable source of information and introduces a qualitative content analysis methodology for wine tourism research. Theoretical implications demonstrate that satisfaction in wine tourism is multidimensional, reinforcing existing theories and expanding knowledge of sensory experiences and motivating factors. Managerially, the findings highlight the critical success factors of wine and related activities, emphasizing the need for continuous improvement. Dissatisfiers, such as waiting time and employee performance, can lead to a competitive disadvantage, while satisfiers like wine tastings and aesthetics present opportunities for enhancing customer satisfaction and gaining a competitive advantage. This research contributes to the body of knowledge by shedding light on the specific determinants of satisfaction and dissatisfaction in wine tourism experiences. It underscores the importance of a customer-centric perspective, validates online reviews as a data source, and enhances understanding of the multidimensional nature of satisfaction in wine tourism. The study offers insights for researchers and managers, suggesting alternative measurement tools and encouraging further exploration of sensory aspects and motivations.